Prevalence and clinical associations of tau in Lewy body dementias: A systematic review and meta-analysis. (November 2020) - Chin, Kai Sin; Yassi, Nawaf; Churilov, Leonid; Masters, Colin Louis; Watson, Rosie
Abstract: Introduction: Alzheimer's disease neuropathologies (amyloid-β and tau) frequently co-exist to varying degrees in Lewy body dementias (LBD), which include dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD). Objectives: To investigate the prevalence of tau in DLB and PDD, and its associations with clinical outcomes. Methods: We searched the major electronic databases using the search term: ("dementia with Lewy bodies" OR "diffuse Lewy body disease" OR "Lewy body variant of Alzheimer's disease") AND ("tau protein" OR "tauopathy" OR "neurofibrillary tangle"), for relevant studies which evaluated tau in LBD. Forty-nine articles met the inclusion criteria for data extraction. Where appropriate, a random-effect meta-analysis was performed to obtain pooled estimates for prevalence and risk ratios (RR) or standardized mean differences (SMD) for clinical features, diagnostic accuracy and cognition. Results: Braak neurofibrillary tangle stage ≥ III was observed in 66% (n = 1511, 95%CI 60%–73%) of DLB and 52% (n = 433, 95%CI 27%–76%) of PDD at autopsy. Abnormal CSF phosphorylated-tau levels were present in 28% (n = 925, 95%CI 25%–31%) of DLB and 15% (n = 172, 95%CI 5%–24%) of PDD cases. Higher tau burden in DLB was associated with reduced likelihood of manifesting visual hallucinations (RR 0.56; 95%CI 0.40–0.77) and motor parkinsonism (RR 0.62; 95%CI 0.40–0.98), lower diagnostic accuracy of DLB during life (RR 0.49; 95%CI 0.38–0.64) and worse cognition prior to death (SMD 0.63; 95%CI 0.46–0.81). Conclusions: Tau is common in LBD and may reduce clinical diagnostic accuracy in people with DLB. Prospective longitudinal studies are needed to understand the roles of co-morbid neuropathologies in Lewy body dementias. Highlights: Tau is a common co-pathology in Lewy body dementias. Tau may be more prevalent in dementia with Lewy bodies than Parkinson's disease dementia. Tau affects the clinical picture in people with dementia with Lewy bodies.